Exome array analysis suggests an increased variant burden in families with schizophrenia - McCarthy, N.; Melton, P.; Ward, S.; Allan, S.; Dragovic, M.; Clark, M.; Morar, B.; Rubio, J.; Blangero, J.; Badcock, J.; Morgan, V.; Moses, Eric; et al. (2016)
The exome array assays rare-but-recurrent, likely deleterious, exonic variants and represents an intermediary between single nucleotide polymorphism (SNP) arrays and sequencing for genetic association studies. Multiplex families with multiple affected individuals may be enriched for disease-associated variants of this class compared to unrelated populations. We present an exome array study of schizophrenia in 99 multiplex families (n = 341, including 118 cases) from the Western Australian Family Study of Schizophrenia (WAFSS).Compared to 55,726 individuals from the DIAGRAM sample not selected for schizophrenia, overall allele frequency of exome variants was higher in the WAFSS (P . <. 2.2E-16). This was pronounced in variants nominally associated (P . <. 0.05) with schizophrenia.Genes harbouring variants present only in WAFSS cases were enriched (FDR-corrected . P = 0.05) for membership of the 'extracellular matrix (ECM) - receptor interaction' biological pathway, adding to evidence that processes affecting the composition or turnover of ECM may contribute to neuropsychiatric disease.We did not find individual variants significantly associated with schizophrenia, although like previous studies, power to detect associations of small effect size was low. Cases did not exhibit a higher burden of variants compared to their unaffected relatives and the finding of previous exome chip studies of unrelated samples that 'schizophrenia gene-sets' were enriched for case-only variants was not replicated in the WAFSS.The higher frequency of moderately rare, exonic variants in these multiplex families compared to a population-based sample may account for some of their genetic liability to schizophrenia, and adds to evidence for a role of exome array variants from previous studies of unrelated samples.